Fruit characteristics and ripening pattern of ten Musa genotypes in a subhumid environment in Nigeria - Tenkouano, A.; Baiyeri, K. (EDP Sciences, 2008)
Conventional evaluation of Musa through multilocation trials has often been carried out to ascertain the yield stability and ecological range of new varieties but, for prospective growers, it is equally important to know the fruit characteristics and ripening pattern of the genotypes. Indeed, fruit characteristics determine consumers’ attitudes towards the new varieties, and the associated market value of these varieties. Materials and methods. The metric traits and ripening pattern of fruits from nine Musa hybrids and one local variety of plantain were evaluated during two cropping seasons in a sub-humid environment in Nigeria. Results. All the traits measured varied with the genotype, but cropping cycle influenced only fruit weight and days to complete senescence of fruits. The interaction between genotype and cropping cycle was significant on fruit weight, fruit length and days to attain four different ripening stages. Most genotypes had better values in the ratoon harvest than in the plant crop. Fruit length and shape of PITA 21 were comparable with those of the local check, but the index of edible proportion was highest in PITA 22. PITA 21 and PITA 26 had the longest green life and total shelf life. Conclusion. The genotypes evaluated in our study revealed different utilization potentials. Also, the better postharvest life of some of the hybrids and comparable metric traits with the local check suggested the high adoption potential of the hybrids.